2017
DOI: 10.2147/cia.s130112
|View full text |Cite
|
Sign up to set email alerts
|

Best strategies to recruit and enroll elderly Blacks into clinical and biomedical research

Abstract: BackgroundHistorically, Blacks have been disproportionately underrepresented in clinical trials. Outcomes associated with low Blacks’ participation in research include poor understanding of the predictors and treatment of the disease, increasing health disparities, poor health equity, and suboptimal wellness of the nation as a whole. To address this gap in research participation, we analyzed our recruitment data to identify the most effective strategies for enrolling older Blacks in clinical trials.MethodsData… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 32 publications
1
46
2
Order By: Relevance
“…A growing literature provides strategies for recruiting diverse populations into clinical trials. For example, studies have shown the importance of building relationships and trust [30], including family referrals and community stakeholders [31], person-to-person outreach, presentations in the community, and face-to-face meetings [32]. More recently, studies have evaluated the use of popular social media platforms (e.g., Twitter, Facebook [18,33]) in recruiting vulnerable populations.…”
Section: Focus On Reach From the Very Beginningmentioning
confidence: 99%
“…A growing literature provides strategies for recruiting diverse populations into clinical trials. For example, studies have shown the importance of building relationships and trust [30], including family referrals and community stakeholders [31], person-to-person outreach, presentations in the community, and face-to-face meetings [32]. More recently, studies have evaluated the use of popular social media platforms (e.g., Twitter, Facebook [18,33]) in recruiting vulnerable populations.…”
Section: Focus On Reach From the Very Beginningmentioning
confidence: 99%
“…Several strategies to build trust within the community were discussed at the Workshop as well as have been published in the literature. Suggestions include formation of a community advisory board to receive community input, use of the perspectives of community members and research participants to guide recruitment strategies, collaborations with area organizations to develop relationships, providing an unmet need to the community, educating care providers about dementia and treatments, encouraging a positive and welcoming attitude among all who will work with participants, and acknowledging the potential stigma of ADRD 57,61,62 . Active engagement in and with the community requires showing up often and motivating community members to engage in all aspects of the research process.…”
Section: Workhop Recommendationsmentioning
confidence: 99%
“…Referrals from trusted friends, family members, or physicians has been shown to positively influence participation in clinical research [16,23]. Additionally, research participants who previously underwent an LP or knew someone who did so were more likely to agree to undergo the procedure [10], indicating that comfort with the procedure may positively influence participation.…”
Section: Analysis Of Factors Associated With Baseline Lp Participationmentioning
confidence: 99%